2012
DOI: 10.1002/ar.22422
|View full text |Cite
|
Sign up to set email alerts
|

Inner Ear Evolution in Primates Through the Cenozoic: Implications for the Evolution of Hearing

Abstract: Mammals are unique in being the only group of amniotes that can hear sounds in the upper frequency range (>12 kHz), yet details about the evolutionary development of hearing patterns remain poorly understood. In this study, we used high resolution X-ray computed tomography to investigate several functionally relevant auditory structures of the inner ear in a sample of 21 fossil primate species (60 Ma to recent times) and 25 species of living euarchontans (primates, tree shrews, and flying lemurs). The structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…As a result, other senses, including improved olfactory sensitivity [86], high-frequency hearing [87] and the development of tactile vibrissae (whiskers) [88], became more acute.…”
Section: Loss Of Visual and Extra-ocular Photoreception And Photorecementioning
confidence: 99%
“…As a result, other senses, including improved olfactory sensitivity [86], high-frequency hearing [87] and the development of tactile vibrissae (whiskers) [88], became more acute.…”
Section: Loss Of Visual and Extra-ocular Photoreception And Photorecementioning
confidence: 99%
“…In other words, we expect the size of middle ear components to covary with that of inner ear structures to a large degree so that the two systems can work as an integrated whole in audition. In turn, the scaling relationship between the organs of hearing and brain/body size seems to be a consequence of the fact that cochlear volume (Kirk and GosselinIldari, 2009) and length (Coleman and Boyer, 2012) are strong determinants of hearing frequency sensitivity. The absolute interspecific variation in size of the hearing organs may therefore be constrained by demands on the auditory system, unlike brain size or body size.…”
Section: By What Criteria Can Ica Branch Size Be Evaluated?mentioning
confidence: 99%
“…3). And even though Tarsiers have more spiral turns and have longer cochleae than Omomyids (Coleman and Boyer 2012), they share with small anthropoids some other aspects of morphology of the cochlea: we found that Tarsius, microchoerines and small anthropoids have anteriorly oriented cochleae exhibiting a second turn staying away from the plane of the first turn, and posteriorly oriented common crura. These three characters are candidate synapomorphies for the inner ears of haplorhines.…”
Section: Morphological Differences Between the Two Primate Subordersmentioning
confidence: 61%
“…Morphological variation of the bony labyrinth across taxa reflects differences in locomotor behavior (Silcox et al 2009;Spoor and Zonneveld 1998;Spoor et al 2007;Walker et al 2008 ) and hearing performance (Coleman and Boyer 2012;Echteler et al 1994;Gleich et al 2005; Kirk and Gosselin-Ildari 2009;West 1985). This structure is thus highly functionally constrained.…”
Section: Have Revived the Hypothesis Of A Special Link Between Adapifmentioning
confidence: 99%
See 1 more Smart Citation